Optimizing The Utilization of E-Commerce-Based Information Technology As A Marketing Media To Increase Sales At Msme Outlets In Lamongan Regency During The Covid-19 Pandemic - Noer Rafikah; Triyana Purnama Sari (Jurnal Sains Sosio Humaniora, 2022)
Micro, Small and Medium Enterprises must have competitiveness in order to survive. WrongOne strategy to increase competitiveness is to use the right marketing media thatcombines offline (conventional) and online marketing media. e-commerce has a positive and significant impact on improving the performance of MSMEs. The purpose of this study is to provide education to MSMEs, especially the MSME outlet community which is the sample in this study, in order to optimize E-Commerce media as a marketing medium. This study uses descriptive qualitative methods by utilizing secondary data derived from key informants, various literatures. such as books, articles, and homepages to access the latest data and information related to various analyzes of optimizing the use of information technology based on E-commerce. This research results that the use of information technology requires a carrying capacity that is not easy. This is evidenced by research, which states that only 20% of MSME Outlet members use the marketplace because there are many requirements that must be met by sellers, namely related to product standardization and legality, which almost 70% of MSME Outlet members still do not fulfill.